2013
DOI: 10.1099/vir.0.055616-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced sphingosine kinase 1 activity in dengue virus type-2 infected cells can be mediated by the 3′ untranslated region of dengue virus type-2 RNA

Abstract: Sphingosine kinase 1 (SphK1) is a lipid kinase with important roles including regulation of cell survival. We have previously shown reduced SphK1 activity in cells with an established dengue virus type-2 (DENV-2) infection. In this study, we examined the effect of alterations in SphK1 activity on DENV-2 replication and cell death and determined the mechanisms of the reduction in SphK1 activity. Chemical inhibition or overexpression of SphK1 after established DENV-2 infection had no effect on infectious DENV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 57 publications
1
25
2
Order By: Relevance
“…1d). This suggests that in our infection system and similar to our prior observation, where increasing SK1 after an infection was established had no effect on DENV replication (Carr et al, 2013a), increased levels of exogenous SK1 prior to DENV challenge also has no significant impact on DENV infection.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…1d). This suggests that in our infection system and similar to our prior observation, where increasing SK1 after an infection was established had no effect on DENV replication (Carr et al, 2013a), increased levels of exogenous SK1 prior to DENV challenge also has no significant impact on DENV infection.…”
Section: Resultssupporting
confidence: 67%
“…The above studies linking high levels of SK with enhancement of viral infection are in contrast to our own observations of a reduction in SK1 activity in response to dengue virus (DENV) infection (Wati et al, 2011), as also reported for the related flavivirus bovine viral diarrhea virus (Yamane et al, 2009). Close analysis of the time-course of the reduction in SK1 in DENV-infected cells demonstrates a correlation with high levels of the DENV 39 UTR, which can compete for the SK1 activator eEF1A (Carr et al, 2013a;Leclercq et al, 2008Leclercq et al, , 2011, which is utilized by flaviviruses to assist replication (Blackwell & Brinton, 1997;Davis et al, 2007). Additionally, our previous data (Carr et al, 2013a;Calvert et al, 2015), as well as that of Yamane et al (2009), suggest an increase in SK1 activity in the early hours following infection.…”
Section: Introductioncontrasting
confidence: 53%
See 3 more Smart Citations